FORMULATION AND TESTING OF SOLID SOAP CONTAINING 96% ETHANOL EXTRACT OF PURSLANE (Portulaca oleracea L.) COMBINED WITH VIRGIN COCONUT OIL (VCO) AGAINST Staphylococcus aureus - Sari, Rose Intan Perma; Rahmah, Anggi Apria Faradisya; Hermansyah, Oky; Rahmawati, Suci; Sipriyadi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Staphylococcus aureus is a pathogenic bacterium commonly associated with various infections. An initial step in preventing and addressing infections is the use of antibacterial soaps. The purslane extract can serve as an antibacterial agent that inhibits the growth of Staphylococcus aureus, while VCO offers additional protection through its antimicrobial properties and ability to maintain skin moisture. This study aimed to formulate a solid soap using 96% ethanol extract of purslane combined with VCO. Purslane powder was extracted using a maceration method. The physical properties of the soap were evaluated, including organoleptic evaluation, PH, homogeneity, foaming capacity, foam stability, and antibacterial activity against Staphylococcus aureus. Based on the results of the physical property evaluations, the solid soap met the required standards. The antibacterial effectiveness test showed inhibition zones for F1 at 3.21 ± 0,023 (weak category), F2 at 4,26 ± 0,102 (weak category), and F3 at 5,2 ± 0,070 (weak category). The results indicate that the purslane extract, in combination with varying amounts of VCO, can be formulated into solid soap that meets the physical property evaluation criteria and possesses antibacterial activity against the growth of Staphylococcus aureus.  Keywords: Solid Soap; Antibacterial; Purslane Plant; VCO; Staphylococcus aureus